Women Empowerment in Rural Sector - Aggarwal, Parul (International Journal of Psychosocial Rehabilitation, 2020)
Women Empowerment in rural areas has been appointed as an indispensable condition to reduce poverty in developing countries like India. Although women make up half of the Indian population, their participation in various activities is not the same as men even today. Without the participation of women in the development process, society as a whole cannot be said to develop sufficiently. In recent decades, the topic of women’s empowerment in rural areas has become acute, especially, in developing countries like India. Rural women are key agents for achieving the sustainable development of India. The present study attempts to analyze the women empowerment in rural India. This paper clearly illustrates the fact that empowering the women is a key not only to the wellbeing of individuals, families and rural communities but also to overall development of the country.